Kewenangan Gubernur DKI Jakarta dalam Penetapan Proyek Infrastruktur Daerah Tahun 2020 s.d. 2025 - Andek Prabowo (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the authority of the Governor of DKI Jakarta in determining regional infrastructure projects for the 2020–2025 period, based on Law No. 23 of 2014 and Law No. 29 of 2007. The Governor holds broad authority in planning and implementing development, particularly in spatial planning, transportation, and population control. During this period, strategic projects such as the Jakarta International Stadium (JIS), MRT–LRT integration, and Formula E were implemented. However, their execution faced challenges, including budget constraints due to the pandemic, land acquisition issues, political dynamics with the Regional House of Representatives (DPRD), and coordination with the central government. The success of these projects depends on inter-agency synergy and national policy support.